Expression of thymidine phosphorylase as an effect prediction factor for uterine cervical squamous cell carcinoma after radiotherapy: an immunohistochemical study. Issue 3 (1st April 2006) - Nakashima, M.; Nakano, T.; Ametani, Y.; Funamoto, H.; Uchiyama, A.; Miwa, A.; Miyata, S.; Shoji, M.; Kondo, T.; Satake, S.; Kojima, Y.
Abstract : Prognoses in cases of uterine cervical squamous cell carcinoma treated with radiotherapy were investigated in association with immunohistochemical expression of an angiogenic factor, thymidine phosphorylase (TP). Forty-six cases of uterine cervical squamous cell carcinoma mainly treated with radiotherapy during 1992–2001 at our clinic were studied. All were diagnosed as stages IIB to IVA. Paraffin-embedded biopsy specimens excised before radiotherapy were stained immunohistochemically using anti-TP monoclonal antibody. The extent of staining in both tumor and interstitial cells was graded as (−), (±), (+), and (2+). Specimens with TP expression levels of (2+) and (+) were regarded as positively stained and those with TP expression levels of (±) and (−) as negatively stained. The efficacy of radiotherapy in both groups was analyzed by the Kaplan–Meier method. With tumor cells, 5-year survival rates for the positive ( n = 38) and negative ( n = 8) staining groups were 73.9% and 42.9%, respectively; the rate being significantly higher for the TP-positive group (log rank, P = 0.0096). Contrarily, with staining for interstitial cells, the 5-year survival rates for the positive ( n = 20) and negative ( n = 26) staining groups were 74.1% and 64.6%, respectively, with no significant difference (log rank, P = 0.406). The efficacy of radiotherapy in the group with positive staining of tumor cells was significantly better than in the negative staining group. Immunohistochemical expression of TP in tumor cells is suggested as a useful prognostic factor for uterine cervical squamous cell carcinomas treated with radiotherapy. Choosing therapy for individual cases by referring to factors including TP expression should contribute to an improved prognosis.